2014
DOI: 10.1371/journal.pone.0088836
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Disorders among Prisoners in the State of Sao Paulo, Brazil

Abstract: ObjectiveTo determine the prevalence of psychiatric disorders in the prison population in the State of São Paulo, Brazil.MethodsThrough stratified random sampling, 1.192 men and 617 women prisoners were evaluated for the presence of psychiatric disorders by the Composite International Diagnostic Interview, 2.1 version, according to definitions and criteria of International Classification of Diseases (ICD-10). The prevalence estimates of mental disorders and their respective 95% confidence intervals were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
59
2
16

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 29 publications
(61 reference statements)
13
59
2
16
Order By: Relevance
“…Consistent with our results, the current reviews have been shown that psychiatric disorders are more prevalent in prisoners than general population (4,22). Andreoli et al in Brazil (2014) reported that a 12-month prevalence of any mental disorder was 39.2% among women, and 22.1% among men which was much lower than the percentage in this study (23). Some divergences in studies can be resolved by difference in the methodological approach.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our results, the current reviews have been shown that psychiatric disorders are more prevalent in prisoners than general population (4,22). Andreoli et al in Brazil (2014) reported that a 12-month prevalence of any mental disorder was 39.2% among women, and 22.1% among men which was much lower than the percentage in this study (23). Some divergences in studies can be resolved by difference in the methodological approach.…”
Section: Discussionsupporting
confidence: 89%
“…Although women in general do not present a violent profile, dangerousness becomes more significant when there is psychiatric morbidity 31 . Thus, the female population of our study presented high psychiatric morbidity, especially with comorbidities, as can be seen in a previous publication 3 .…”
Section: Discussionsupporting
confidence: 70%
“…Mental illness in prison institutions as a result of prison confirnment, 1 is a public health issue recognized worldwide, especially due to the high prevalence of depression 2,3 . This, in turn, leads us to think about the strong association with suicidal behavior 4,5 , worsening health conditions and issues regarding the re-socialization of prisoners after release.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates in this admission study point to much higher numbers than reported in studies of existing prisoners from Chile, South America (Pondé et al 2011;Mundt et al 2013;Andreoli et al 2014) and from other emerging countries (Adesanya et al 1997;Assadi et al 2006;Colmenares Bermúdez et al 2007;Zahari et al 2010;Naidoo & Mkize, 2012). Prevalence rates in this admission study point to much higher numbers than reported in studies of existing prisoners from Chile, South America (Pondé et al 2011;Mundt et al 2013;Andreoli et al 2014) and from other emerging countries (Adesanya et al 1997;Assadi et al 2006;Colmenares Bermúdez et al 2007;Zahari et al 2010;Naidoo & Mkize, 2012).…”
Section: Interpretation and Comparison With The Literaturecontrasting
confidence: 45%